Experimental and theoretical studies of C–H⋯M interactions in palladium and platinum complexes derived from 1,2-bis-(2-hydroxymethylphenylthio)ethane - González Montiel, Simplicio (2015)
The molecular structures of several related cis-[j2-SS-(L)MHal2] compounds 1, 1DMSO, 2, 2H2O, 3DMSO, 4 and 5 where L = HOCH2Ph-S-CH2-CH2-S-PhCH2OH, M = Pd or Pt, and Hal = Cl or Br or I, were analyzed by single crystal X-ray diffraction analyses. In all complexes, the presence of intramolecular C–HM (M = Pd or Pt) interactions with distance values of 2.687–2.914 Å was established. In solid state both syn- or anti-conformers exist; this suggests that one or two ortho-hydrogen atoms on the phenyl rings are close to the metal. Furthermore, the existence of these weak interactions induce a significant effect on the geometry adopted by the metal center. The crystal structures show a wide variety of intermolecular noncovalent bonding such as hydrogen bonds, MM contacts, p-p, C–Hp and Halp interactions. For all the complexes, the structural analysis performed by Density Functional Theory (DFT) is in good agreement with parametric data obtained from X-ray measurements. Topological analyses of the electron density function [q(r)], which have been performed according to Bader’s Atoms in Molecules theory, reveal bond critical points relating the metal atom with aromatic ortho-hydrogen atoms. Laplacian r2 q(r) and density q(r) values indicate formation of the weak anagostic C–HM interactions